Role of aliphatic hydrocarbon content in non-solvating porogens toward porosity of cross-linked microbeads - Mane, Sachin; Badiger, Manohar V.; Rajan, C. R.; Ponrathnam, Surendra; Chavan, Nayaku (Polymer, 2016)
Megaporous spherical acrylate copolymer beads were synthesized by suspension polymerization using non-solvating porogens. Non-solvating porogens with higher aliphatic hydrocarbon content generated megaporous morphology with lower surface area. Surface area increased and inversely megaporosity was decreased with decrease in the aliphatic hydrocarbon content of porogen. Megaporosity (5.47 mu m) and pore volume of 5.52 cm(3)/g was obtained with n-decanol. Thermal property of copolymer is a function of type (rigidity/flexibility/elemental composition) and concentration (cross-link density) of monomer and cross-linker. Copolymer containing rigid cross-linker (divinylbenzene) had better thermal stability over copolymer with flexible cross-linker (ethylene dimethacrylate). Further, higher concentration of rigid cross-linker or lower concentration of flexible cross-linker enhanced the thermal stability. Porous polymers are potentially recognized as a solid support for solid-phase synthesis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cross-linked microbeads; Interfacial tension; Megaporosity; Non-solvating porogens; Thermal properties